Internal Organization Analysis Of Unilever - Adi Neka Fatyandri; Defen; Deviana Lie; Jason; Jesty; Jolin (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The outbreak of Covid-19 in 2020 has brought downturn to the global economy and many companies went bankrupt during the epidemic. However, according to Unilever's financial report for the first half year, its sales fell only by 1.6% and its financial situation is still stable. The reason for it is not only for Unilever's action of taking Covid-19 as normalization, but also for its differentiation strategies, which make Unilever a competitive enterprise when the consumer products are in demand in Covid-19. Through the literature research method, this article uses the combination of SWOT (strengths, weaknesses, opportunities and threats) and PEST (political, economic, social and technological factors) models to explore the internal and external environments of Unilever in 2020, and concludes that under the multiple impacts of the external environment, Unilever still has great opportunities to make development relying on its own excellent internal conditions.